Cellular internalization mechanism of novel Raman probes designed for plant cells. Issue 4 (20th August 2020) - Midorikawa, Keiko; Tsuchiya, Kousuke; Law, Simon Sau Yin; Miyagi, Yu; Asai, Takuya; Iino, Takanori; Ozeki, Yasuyuki; Kodama, Yutaka; Numata, Keiji
Abstract : Diphenyl acetylene derivatives containing various polymeric components have been designed as new Raman imaging probes. These are taken up by plant cells via different pathways, and the internalization of exogenous molecules can be visualized. Abstract : Diphenylacetylene derivatives containing different polymeric components, poly(l -lysine) (pLys) or tetra(ethylene glycol) (TEG) were designed as novel Raman imaging probes with high Raman sensitivity and low cytotoxicity in living plant cells. The pLys-conjugated probe is internalized via an endocytosis-dependent pathway, whereas TEG-conjugated probe most likely induces direct penetration into the plant cells.